1989
DOI: 10.1111/j.1600-0749.1989.tb00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Approaches to a Carboranyl Thiouracil

Abstract: Thiouracil is selectively incorporated into melanotic murine melanomas during melanin synthesis. This selectivity makes thiouracil a likely vehicle for boron in the diagnosis and therapy of melanoma. Several synthetic routes to thiouracils bearing an alkyl decacarboranyl group attached to various positions on the ring have been investigated. The successful syntheses of three new alkynyl thiouracils and the conversion of one of them into a carboranyl thiouracil are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Spectral data of 1a, 3a agreed with the literature [51]. Pyrimidine derivatives 8d, 8e, 8g were synthesized according to the known protocols [37,38]. Spectral parameters of 8e and 8g agreed with those presented in Refs.…”
Section: Starting ω-Alkyne Substituted Pyrimidinessupporting
confidence: 80%
See 2 more Smart Citations
“…Spectral data of 1a, 3a agreed with the literature [51]. Pyrimidine derivatives 8d, 8e, 8g were synthesized according to the known protocols [37,38]. Spectral parameters of 8e and 8g agreed with those presented in Refs.…”
Section: Starting ω-Alkyne Substituted Pyrimidinessupporting
confidence: 80%
“…6-Methyluracil derivatives 8g,h,i with a ω-alkyne substituent at the C5 atom were prepared in three steps by analogy with procedures earlier described [ 37 , 38 ]. Initially, ethylacetoacetate was alkylated in a solution of sodium in ethanol by treatment with (a) propargyl bromide to prepare ethyl 2-acetyl-4-pentynoate 8a ; (b) 5-iodo-pent-1-yne to prepare ethyl 2-acetyl-6-heptynoate 8b ; (c) 6-iodo-hex-1-yne to prepare ethyl 2-acetyl-7-octynyloate 8c (Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have shown that thiouracil is strongly taken up by melanotic melanoma in murine models (32,33), and in vitro experiments indicate that both high tyrosinase and melanin levels are required for enhanced incorporation (34). Boron containing thiouracils have been synthesised in Altstralia (Wilson 1989) and Germany (Gabel et a1 1990), and tested in syngeneic and nude mice models with murine and human melanomas . Therapeutic boron concentrations in the tumour and tumour to liver boron ratios of 10 have been achieved.…”
Section: E) Boron Containing Thiouracilmentioning
confidence: 99%
“…Several synthetic routes and false trails have been previously reported (Allen et al, 19861, and current efforts are directed to the conjugation of an alkyl decacarbor-any1 group attached to various positions on the ring (Wilson, 1989). While the synthesis of a carboranyl thiouracil is the primary objective, a thiouracil containing an alkynyl (i.e., a triple bond alkyl group) has been achieved.…”
Section: Boron Chemistrymentioning
confidence: 99%